(untitled) (Global Journal of Management and Business Research, 2018)
The purpose of this study was to determine the effects of tax audit on revenue collection in Rwanda. The study is limited to the 110 respondent of Headquarter of the Rwanda Revenue Authority (RRA) in Kigali. The study adopted a descriptive approach.Both Primary and secondary data was used and then analyzed through SPSS version 21. Data analysis involved statistical computations for averages, percentages, and correlation andregression analysis. Ordinary least squares (OLS) regression method of analysis was adopted to determine the inferential statistics. From the findings, tax administration, tax revenue performance, revenue protection system, tax automation to a constant zero, revenue collection would be at 0.347. A unit increase on Tax administration would lead to increase in revenue collection by a factor of 0.162, a unit increase in tax revenue performance would lead to increase in revenue collection by a factor of 0.282, a unit increase in revenue protection system would lead to increase in revenue collection by a factor of 0.194 and unit increase in tax automation would lead to increase in revenue collection by a factor of 0.211. Therefore Tax audit actually has an effect to revenue collection as according to the t – tests there is significance in the correlation between tax collected before the audit and after the audit. This clearly indicates that tax audit increases revenue collection. That in essence means that the more the tax audit conducted the more revenue is collected.There is a need for a study on how the size of a company influences the auditing as there is variation for various organizations based on the size.